APRESIASI MASYARAKAT ETNIS TIONGHOA TERHADAP KESENIAN KARAWITAN JAWA PADA PAGUYUBAN RAHAYU RARAS DI KOTA PEKALONGAN - handayani, yuninda (Jurnal Seni Musik, 2014)
The research problems are include (1)Ã‚Â  How is the cooperative model type talking stick which is helped multimedia quiz creator to improve the senior high school studentsÃ¢â‚¬â„¢ folklore attentive skill. (2) how is the principles of cooperative model type talking stick development which is helped by multimedia quiz creator to improve theÃ‚Â  senior high school studentsÃ¢â‚¬â„¢ folklore attentive skill. This research uses research and development design (R&D), this research developes model whichÃ‚Â  have been exist that is cooperative model type talking stick into cooperative model type talking stick which is helped by multimedia quiz creator. The results of the researches are : (1) the teacher and studentsÃ¢â‚¬â„¢ need toward to cooperative model type talking stick which is helped by multimedia quiz creator. (2) cooperative model type talking stick priciples are (a) innovative learning strategy, (b) innovative learning media, (c) assessment. Ã‚Â